Penyusunan Laporan Keuangan Berdasarkan SAK EMKM (Studi Kasus Pada UMKM Edward Konveksi) - Rizky Cahya Maulana; Vina Citra Mulyandani (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Micro Small and Medium Enterprises (MSMEs) in Indonesia have a significant role in building the country's economy. But until now there are still many MSMEs that are difficult to grow their business. One of the contributing factors is that there are still many MSMEs who do not realize the importance of compiling financial statements as a tool to measure the company's performance and as a matter of consideration in making decisions. This research is aimed at MSMEs who have not made financial statements. MSMEs Edward Konveksi is one of the convection companies that has not yet made financial statements. The purpose of this research is to find out the financial records that have been done Edward Konveksi, and compile financial statements based on SAK EMKM. The research method used is a qualitative descriptive method. Data collection techniques are interviews, observations and documentation. This research shows that MSMEs Edward Konveksi have not made financial records and have not compiled financial statements based on SAK EMKM.